Development of a mathematical model for animal cell culture without pH control and its application for evaluation of clone screening outcomes in shake flask culture - Gadgil, Mugdha (Journal of Chemical Technology and Biotechnology, 2015)
BACKGROUNDCurrently used mathematical models for animal cell growth and metabolism cannot simulate changing culture pH and its effect on metabolism, and hence cannot accurately model cultures lacking pH control. Animal cell cultures are however widely cultured at a small scale without pH control, e.g. for clone screening during cell line development. A mathematical model for animal cell growth without pH control is developed and applied to design optimal conditions for clone screening without pH control. RESULTSThe mathematical model successfully simulates published data for suspension CHO culture in shake flasks. It is further used to simulate clonal heterogeneity and predict relative clone performance in different culture conditions. Predictions of correlation coefficients between clone titers in batch and fed batch screening conditions and pH controlled fed batch agree with published values. Fed batch mode is predicted to give better screening outcomes than batch, but only for clones able to consume lactate. Simulations reveal that culture duration of the screening assay has a large effect on the screening outcome and optimal durations differ based on the ability or inability of clones to consume lactate. CONCLUSIONThis study presents a tool for optimal design of screening assay for clone selection without pH control. (c) 2014 Society of Chemical Industry
Keywords: clone screening; clone selection; culture duration; high throughput screening; lactate consumption; mathematical model with pH effects; pH control for animal cell culture

Differential responses of CHO cells adapted to limitation of inorganic phosphate, glucose or glutamine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (255th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nexus of Food, Energy, and Water, 2018)